The Influence of Early Temperament on Language Development: The Moderating Role of Maternal Input - Spinelli, Maria; Fasolo, Mirco; Shah, Prachi E.; Genovese, Giuliana; Aureli, Tiziana (Frontiers in Psychology, 2018)
Temperament is an individual aspect that strictly affects infants and children engagement with the environment and it is supposed to play a role in the acquiring of new competences. Several studies focused on the possible influence of temperament in the process of language acquisition in early childhood reporting not consistent findings. Since maternal input is a variable that has been widely associated with infant language development this longitudinal study aimed to explore the role of the quality of maternal input in the temperament-language association. We hypothesized that the longitudinal association between early infant temperament and language production is moderated by the quality of maternal input during the first year of life. Infant temperament at 3 months and maternal linguistic input (lexical diversity and syntactic complexity) during spontaneous mother–infant interactions at 6, 9, and 12 months were assessed. Language competences were evaluated at the end of the second year: language production at 18 months with the CDI and child syntactic complexity at 24 months during spontaneous speech. Results showed significant moderating effects of syntactic complexity and lexical variability of maternal input at 6 and 9 months on the association of duration of orienting abilities and later language production. Infants with greater attentional abilities and with mothers who spoke to them with a more complex and variable input showed the better language outcomes. The association between infant distress to limitations and child language was not moderated by maternal input. No effects were found when considering the temperamental scale smile and laugher. Attentional control temperamental characteristics could help the infant to be more focus on maternal input throughout the first year of life and could consequently facilitate language development. Our findings underlined the necessity to explore infant development considering the interaction between individual and contextual factors.